2021
DOI: 10.3390/microorganisms9020458
|View full text |Cite
|
Sign up to set email alerts
|

The Autotrophic Core: An Ancient Network of 404 Reactions Converts H2, CO2, and NH3 into Amino Acids, Bases, and Cofactors

Abstract: The metabolism of cells contains evidence reflecting the process by which they arose. Here, we have identified the ancient core of autotrophic metabolism encompassing 404 reactions that comprise the reaction network from H2, CO2, and ammonia (NH3) to amino acids, nucleic acid monomers, and the 19 cofactors required for their synthesis. Water is the most common reactant in the autotrophic core, indicating that the core arose in an aqueous environment. Seventy-seven core reactions involve the hydrolysis of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 88 publications
2
29
0
Order By: Relevance
“…To see whether PP i might have had a role in primordial energetics, the reactions of the core ( Wimmer et al, 2021 ) that involve PP i or ATP were identified and polarized in the biosynthetic direction, that is, from H 2 and CO 2 toward cell mass synthesis. In Lipman’s view, PP i was an environmental energy source, a substrate that assumes a thermodynamic role as an educt residing on the left side of an enzymatic reaction, while in Kornberg’s view PP i is synthesized in metabolism via ATP hydrolysis and assumes a kinetic role as a product that is removed from the right side of the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To see whether PP i might have had a role in primordial energetics, the reactions of the core ( Wimmer et al, 2021 ) that involve PP i or ATP were identified and polarized in the biosynthetic direction, that is, from H 2 and CO 2 toward cell mass synthesis. In Lipman’s view, PP i was an environmental energy source, a substrate that assumes a thermodynamic role as an educt residing on the left side of an enzymatic reaction, while in Kornberg’s view PP i is synthesized in metabolism via ATP hydrolysis and assumes a kinetic role as a product that is removed from the right side of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Note that these calculations entail only biosynthetic costs and do not consider energy spilling ( Tempest and Neijssel, 1984 ) or maintenance energy, which can exceed biosynthesis by a factor of 3 in exponential growth ( Russell and Cook, 1995 ; Russell, 2007 ), and by more under energy limitation ( Lever et al, 2015 ). b The proportion of PP i forming steps in monomer biosynthesis was calculated as the total cost for the monomer multiplied by the fraction of PP i forming steps among ATP hydrolyzing steps en route to nucleoside monophosphates ( Wimmer et al, 2021 ). c The proportion of PP i forming steps in polymerization takes the costs of proofreading, assembly and modification from Lever et al (2015) into account.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It of course depends on who one asks and where one thinks how life might have arisen. If life arose from the reaction of H 2 and CO 2 in hydrothermal vents [103,125], as we contend, then its structure emerges from the geometry of carbon bonds as carbon oxides undergo reduction with electrons and hydrides from H 2 , reacting to generate longer and more diverse carbon chains [9] while reacting with other elements like nitrogen and sulfur to produce the amino acids, nucleosides, and cofactors that comprise life [127,128], through overall reactions that are thermodynamically favored [129] under the conditions of hydrothermal vents.…”
Section: Discussionmentioning
confidence: 99%